A Comprehensive Systematic Review of The Impact of HIV/AIDS on Ocular Manifestations: A Focus on HIV Retinopathy and Opportunistic Infections such as Cytomegalovirus (CMV) Retinitis - Dewi Dwipayanti Giri; Ray Ratnansari Giri (International Medical Journal Corp. Ltd, 2025)
Introduction: Ocular complications represent a significant cause of morbidity in individuals with advanced Human Immunodeficiency Virus/Acquired Immunodeficiency Syndrome (HIV/AIDS). Among these, Cytomegalovirus (CMV) retinitis stands as the most prevalent and vision-threatening intraocular opportunistic infection. Its pathogenesis is intrinsically linked to the state of severe immunosuppression induced by HIV, particularly the depletion of CD4+ T lymphocytes. While the advent of combination Antiretroviral Therapy (ART) has dramatically altered the epidemiology and prognosis of CMV retinitis, it remains a persistent clinical challenge, especially in resource-limited settings and among patients presenting with late-stage HIV disease. This systematic review synthesizes contemporary evidence to delineate the epidemiological burden, pathophysiological determinants, diagnostic standards, therapeutic efficacy, and clinical outcomes associated with CMV retinitis in the global HIV/AIDS population. Methods: A comprehensive systematic review was conducted utilizing the PubMed, Google Scholar, Semantic Scholar, Springer, Wiley Online Library search engine, which interrogated over 138 million academic papers from databases iScreening criteria mandated that studies include an HIV/AIDS population, examine HIV retinopathy or opportunistic ocular infections (especially CMV retinitis) as outcomes, report quantitative data on the relationship, and employ appropriate designs (observational studies, systematic reviews, or meta-analyses). Additional filters ensured clear HIV diagnosis criteria, focus on HIV-positive patients, adequate sample size (>10), and peer-reviewed full-text status. The final analysis and this report are based on the 40 sources with the highest screening scores. Data extraction encompassed: study design and setting; detailed HIV population characteristics (CD4+ count, ART status); ocular manifestation prevalence and features; associated risk factors; diagnostic methodologies; treatment interventions (systemic, local, combination); clinical outcomes (visual acuity, progression, survival); and geographic/healthcare context. Results: The analysis of 40 studies confirms CMV retinitis as the dominant ocular opportunistic infection in AIDS, with a pooled prevalence of 14.0% (95% CI: 11.8%-16.2%) in low- and middle-income countries (LMICs), and historically affecting 20-40% of AIDS patients pre-ART. The degree of immunosuppression is the paramount risk factor, with 73.4% of CMV retinitis cases occurring at CD4+ T cell counts below 50 cells/μL. Vision loss affects approximately one-third of patients (31.6%, 95% CI: 27.6%-35.8%). Treatment efficacy varied: the ganciclovir implant provided the longest median time to progression (221 days), significantly outperforming intravenous ganciclovir (71 days) (Musch et al., 1997). Combination systemic therapy (foscarnet + ganciclovir) was superior for relapsed disease (Sha, 1996). The introduction of ART, particularly protease inhibitors, fundamentally modified outcomes, reducing inflammation recurrence from 33% in untreated to 10% in ART-treated patients. For patients achieving sustained immune reconstitution (CD4 >75 cells/μL on HAART for ≥18 months), discontinuation of CMV maintenance therapy was safe with a 48-week relapse probability of only 2.2% (Wohl et al., 2005). Critically, early screening and diagnosis (CD4 <100 cells/μL) resulted in significantly better baseline visual acuity (median 20/30 vs. 20/80 for late diagnosis), underscoring that timing is a crucial determinant of visual prognosis (Ausayakhun et al., 2018). Discussion: The evidence unequivocally establishes that the risk of CMV retinitis is mediated almost exclusively by the depth of HIV-associated immunosuppression. The persistent high burden in certain settings, despite ART availability, is directly attributable to late presentation and diagnosis of HIV, at which point patients have already crossed the critical immunologic threshold. ART serves as the most effective prophylactic and therapeutic intervention by enabling immune recovery. The evolution of treatment—from systemic antivirals to local sustained-release devices—reflects a pursuit of maximizing intraocular drug levels while managing systemic toxicity. However, a key paradigm elucidated is that local therapy alone, while excellent for controlling the treated eye, may inadequately protect the contralateral eye and systemic sites, favoring combined local-systemic strategies where feasible (Martin et al., 1999; D. Jabs, 2001). The review also highlights the critical disparity between resource settings, where access to costly implants or oral valganciclovir may be limited, making intravitreal injection protocols a vital, effective alternative (Liang et al., 2023; Teoh et al., 2012). The irreversible nature of retinal necrosis makes early detection through systematic screening the single most important modifiable factor for preserving vision. Conclusion: CMV retinitis remains a serious complication of advanced HIV/AIDS, serving as a clinical marker of severe immunosuppression. Its management is multifaceted, requiring: 1) early HIV diagnosis and prompt initiation of ART for prevention; 2) regular ophthalmologic screening of high-risk patients (CD4+ count <100 cells/μL); 3) a tailored treatment approach that balances local disease control with systemic protection, considering resource availability; and 4) in the context of successful immune reconstitution, consideration for discontinuing maintenance therapy with appropriate monitoring. The goal of modern management is not merely to treat retinitis but to preserve vision and quality of life through integrated HIV and ophthalmologic care.